Auto-Rickshaw Drivers and Their Livelihood in Baglung, Nepal - Panta, Saroj Raj; Silwal, Sudarshan (International Research Journal of MMC, 2026)
This research paper analyzes the socioeconomic background and survival issues of auto rickshaw drivers of Baglung Bazaar both by quantitative and qualitative methods. Explanatory and exploratory sequential research is used. Survey, observation, interview and case study data and information were collected. The total 98 auto drivers were there, out of them 60 auto drivers were selected using a simple random sampling of Baglung Bazzar in the year 2024 to find out the facts of their livelihood after adopting this occupation. The aim is to provide voices in favor of legalizing rickshaws and e-rickshaws in the city, and provide policy suggestions on enhancing safety and efficiency. Massive fleet growth in the rickshaw sector has resulted in earnings crumbling and there is more traffic risk through over-competition. If properly controlled rickshaws, rickshaws would be able to serve an effective purpose in urban planning, gather government revenues, and enhance road infrastructure for transport. On the basis of assessment, the study identified the socio-economic impacts of diesel and battery rickshaws and validated that 80% of operators are content with the profession. Recommendations of the paper focuses to self-reliance, service quality, and addressing workforce migration to enhance livelihoods and guide policy formulation. More research must be done to formulate a regulatory framework. This study will be useful for future researchers and policymakers dealing with this problem.